Analisis Keberhasilan Resolusi Jihad Nahdlatul Ulama (NU) Dalam Perjuangan Kemerdekaan Republik Indonesia - Jafar Ahmad (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
The jihad resolution initiated by the founder of Nahdlatul Ulama( NU), Haddratus Shaykh Hashim Asyari, at the beginning of the independence of the Republic of Indonesia (October 1945), proved successful in moving the Islamic masses to fight the Dutch invaders who tried to return to ride the allies in Surabaya. An unequal battle against a heavily armed foreign army The question is, why did the resolution of jihad work? What factors can mobilize the Muslim masses so as to welcome the resolution of jihad? Will the resolution of jihad remain relevant if it is implemented in the present or in the future? The data in this research was obtained through literature reviews, both in indexed journals and book reviews, and by analyzing information in a number of mass media. The findings of this research indicate the success of the resolution of jihad in mobilizing the Islamic masses during the independence period because of a number of things. First, the momentum of the proclamation of August 17, 1945. The moment made all Indonesian people solid, especially Islam. Second, the massive mobilization of resources among Islamic boarding schools, especially the formation of militant masses due to the growth of a kind of belief that welcoming the resolution of jihad is mandatory and when syahid will be rewarded with Paradise. Third, the success of the framing of the fatwa of jihad was because it was initiated by high-reputed scholars and then spread massively by scholars through boarding schools so as to stimulate collective action.